VILLAGE HEAD'S LEADERSHIP IN IMPLEMENTING COMMUNITY EMPOWERMENT IN KARANGKAMIRI VILLAGE, LANGKAPLANCAR DISTRICT, PANGANDARAN DISTRICT - Maya Rahmawati; Regi Refian Garis; Asep Nurdin Rosihan Anwar (Yayasan Panca Bakti Wiyata Pangandaran, 2023)
This research was motivated by the lack of optimal implementation of Community Empowerment in Karangkamiri Village, Langkaplancar District, Pangandaran Regency, as well as the leadership of the village head in implementing community empowerment in Karangkamiri Village, Langkaplancar District, Pangandaran Regency. The role of a leader is very necessary in setting goals, allocating scarce resources, focusing training on organizational goals, coordinating changes that occur, building interpersonal contact with followers, and determining the right or best direction if failure occurs. The research method used in this research is qualitative. The qualitative method is a research method based on the philosophy of postpotivism, used to research the conditions of natural objects, as opposed to experiments where the researcher is the key instrument, data collection techniques are carried out in a triangulated/combined manner, data analysis is inductive/qualitative, and the research results are qualitative. emphasizes meaning rather than generalization. This research aims to determine the level of success of the village head's leadership as the leader of the village government in implementing community empowerment. Based on research results, the Village Head's Leadership in Implementing Community Empowerment in Karangkamiri Village, Langkaplancar District, Pangandaran Regency has generally not been implemented optimally because there are obstacles, such as: Lack of utilization of existing potential resulting in a lack of harmony and balance for community empowerment in Karangkamiri Village, Langkaplancar District, Pangandaran Regency. , Lack of adequate budget provision to carry out community empowerment, this is hampered by budget arrangements so that it influences the implementation of community empowerment, Lack of communicators to increase knowledge and skills in community empowerment activities so that people are not creative, for example there is a lack of socialization and counseling in all areas of empowerment on an ongoing basis. routinely to the community